AUDIO-VISUAL MEDIA IN LEARNING - Fuady, Rizal; Mutalib, Ariffin Abdul (Journal of K6, Education and Management, 2018)
This article was created with the aim to expand the knowledge of audio-visual media as a medium for channeling messages and information in learning. Well-designed audio-visual learning media will help achieving learning goals. Each type of learning audio visual media has characteristics, advantages and disadvantages. The use of audio-visual learning media able to facilitate the learning process and optimize the contents of learning materials.